1992
DOI: 10.1007/bf00023511
|View full text |Cite
|
Sign up to set email alerts
|

Effect on leaf photosynthetic rate by leaf blast for rice cultivars with different types and levels of resistance

Abstract: SummaryThe effect of an inoculation with Pyricularia oryzae (isolate P06-6) on net leaf photosynthetic rate of rice ( Oryza sativa) was studied with four cultivars. Measurements were taken on the sixth leaf of the main culm of plants in the early tillering stage. On cultivars C039, IR50 and IR64 a susceptible infection type developed, but a clear difference in relative infection efficiency of the cultivars was observed. The highest number of lesions developed on leaves of C039, whereas the lowest number was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
2
16
0
5
Order By: Relevance
“…Consistent with the results in the current study, Bastiaans and Roumen (1993) reported that the photosynthetic competence of rice (Oryza sativa L.) plants were similar among three rice cultivars with a wide range in relative infection effi ciency (proportion of sporulating lesions) of rice leaf blast (Pyricularia oryzae). The resistance gene from Hyuuga was eff ective in changing the lesion type, reducing disease severity, and eliminating sporulation in the RIL GO1-PR68.…”
Section: Impact Of Soybean Rust On Leaf Photosynthetic Competence-rolsupporting
confidence: 91%
“…Consistent with the results in the current study, Bastiaans and Roumen (1993) reported that the photosynthetic competence of rice (Oryza sativa L.) plants were similar among three rice cultivars with a wide range in relative infection effi ciency (proportion of sporulating lesions) of rice leaf blast (Pyricularia oryzae). The resistance gene from Hyuuga was eff ective in changing the lesion type, reducing disease severity, and eliminating sporulation in the RIL GO1-PR68.…”
Section: Impact Of Soybean Rust On Leaf Photosynthetic Competence-rolsupporting
confidence: 91%
“…When plants are attacked by pathogens, physiological and photosynthetic properties are often impaired (Guo et al 2005;Swiech et al 2001). A number of studies have shown that pathogen infection leads to a decrease in photosynthesis rates (Bastiaans 1991;Bastiaans and Roumen 1992;Berger et al 2007;Chou et al 2000;Domiciano et al 2009) and modifications of the photosynthetic apparatus (Lichtenthaler and Miehé 1997). These modifications can be due to negative regulation or damage to the photosynthetic apparatus.…”
Section: Introductionmentioning
confidence: 96%
“…When plants were infected by pathogens, physiological and photosynthetic properties and growth of plants were negatively influenced (Chia and He 1999;Swiech et al 2001;Guo et al 2005). Most studies showed that pathogen infection led to a decrease in photosynthesis (Bastiaans 1991;Ogren and Evans 1992;Bastiaans and Roumen 1993;Chou et al 2000;Berger et al 2004) and modification or damage of the photosynthetic apparatus (Lichtenthaler and Miehé 1997) which might be the result of a down-regulation of photosynthesis or damage of the photosynthetic apparatus. Both of maximum/ potential quantum efficiency (F v /F m ) and the maximum primary yield (F v /F 0 ) of photochemistry of PS II are related to photosynthetic efficiency of plant leaves (Shangguan et al 2000).…”
Section: Introductionmentioning
confidence: 97%